The development of pragmatic quality model for software product certification process - Yahaya, Jamaiah; Deraman, Aziz; Hamdan, Abdul Razak (2006)
The emergence of Multimedia Super Corridor (MSC) in Malaysia in 1996 was the starting point for the blooming of software and ICT related companies. Despite that, not much attention was given to the quality of the software product that was being developed by different categories of companies. These companies could not justify the quality of their products to the users and the users are left with uncertainties on the quality of the software. Our previous survey identified the need for independent software assessment and certification. Therefore, we propose a conceptual model of software certification process by product quality approach. It is designed to be applied by an independent certification body or any appointed institution. The main focus of this paper is the development of pragmatic quality model that will be applied in the certification process.